"الرحلة الحجازية" للقاضي محمد سليمان المنصوربوري: دراسة وتحليل: "The Hijaz Journey" by Qazi Muhammad Suleiman Al-Mansurpuri: Study and Analysis - Hafiz Muhammad Tahir; Dr Muhammad Ismail (jihat-ul-islam, 2023)
Hajj travels to Makkah Al-Mukarramah are among the topics that occupied a prominent place among Muslims, and the Islamic peoples produced abundant literature in this art in Arabic, Persian, Urdu and other languages. It considers the Two Holy Mosques an important source of historical sources, and solid scientific material, that can help us identify many important aspects of the history of the Two Holy Mosques and their influence on the Muslims of the Indian subcontinent because this vital region of the world represents an important attraction point for Asians in general and for Muslims of the Indian subcontinent in particular, and I will address in my this research "The Hijaz Journey" by Qazi Muhammad Suleiman Al-Mansurpuri.